Kedudukan Hukum Tenaga Medis dan Tenaga Kesehatan Perawat Sebagai Pemangku Profesi Kesehatan Dalam Pelayanan Kesehatan - Hotma P. Sibuea; Dwi Seno Wijanarko; Ali Johardi Wirogioto; Erwin Syahruddin; Katrina Siagian (KRTHA BHAYANGKARA, 2023)
Health professions recognized autonomously by law consist of (1) the medical profession, (2) nursing, and (3) midwifery. These three health professions have different legal principles, so both types of professions have professional autonomy. The professional autonomy of health professions has consequences for various aspects of the existence of health profession stakeholders, such as their position, function, tasks, authority, and legal responsibilities. One of the legal aspects of health profession stakeholders is the legal standing of each health profession stakeholder. The law does not regulate the legal standing of health profession stakeholders in healthcare services, resulting in a legal vacuum regarding the legal standing of these health profession stakeholders. Do health profession stakeholders have equal or different legal standing in healthcare services from the perspective of the principle of legal equality? The research method used is the juridical-normative research method, which examines primary, secondary, and tertiary legal materials. The research conclusion is that the legal standing of health profession stakeholders is the same and equal from the perspective of the principle of legal equality. The suggestion presented is that legislators need to amend healthcare laws, medical practice laws, nursing laws, and midwifery laws to regulate and establish the legal standing of health profession stakeholders as the same and equal based on the principle of legal equality.